2019
DOI: 10.1002/jia2.25408
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of a long‐acting injectable HIV prevention product among US and African women: findings from a phase 2 clinical Trial (HPTN 076)

Abstract: IntroductionHigh HIV incidence and low adherence to daily oral PrEP among women underscore the need for more acceptable and easier to use HIV prevention products. Global demand for injectable contraception suggests that new, long‐acting, injectable formulations could meet this need. We examine acceptability of a long‐acting injectable PrEP among HIV‐uninfected women in Zimbabwe, South Africa and two United States phase 2 trial sites.MethodsQuantitative surveys were administered at the first, fourth and sixth i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 45 publications
0
51
0
Order By: Relevance
“…Over the injection phase of the trial, 27 participants permanently discontinued injectable product use. Stated reasons for discontinuation included product-related side effects, inability or unwillingness to follow study procedures, abnormal lab values, reactive HIV tests, and desire for pregnancy or to terminate the study [ 20 ]. In a supplemental analysis, we found a significant inverse association between participants’ perceived acceptability of pain and discontinuation; participants with higher acceptability of pain had a lower risk for discontinuation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the injection phase of the trial, 27 participants permanently discontinued injectable product use. Stated reasons for discontinuation included product-related side effects, inability or unwillingness to follow study procedures, abnormal lab values, reactive HIV tests, and desire for pregnancy or to terminate the study [ 20 ]. In a supplemental analysis, we found a significant inverse association between participants’ perceived acceptability of pain and discontinuation; participants with higher acceptability of pain had a lower risk for discontinuation.…”
Section: Resultsmentioning
confidence: 99%
“…Both FIIP and ever use of injectable contraception were particularly high among females in non-U.S. settings, findings which were also reflected in phase 2 trial of RPV LA [ 20 ]. In several past HIV prevention trials of oral or topical products among African females, low adherence has been attributed to low HIV risk perception, females’ concerns about stigma, and challenges disclosing to partners compounded by the need to use a product daily [ 29 32 ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…MSW's recommendations for PrEP education in places where men congregate and PrEP delivery through key people (chiefs, councilors, local health workers) or key institutions (schools, workplaces) would have to be trialed to determine appropriateness regarding regular HIV-testing and confidentiality. MSW's preference for less frequent PrEP such as injectables has also been depicted in women-focused studies as aiding adherence [54,55], while on-demand oral PrEP has so far been trialed and proved effective for MSM [56], yet could also widen MSW's PrEP choices. MSW further suggested to include more counselling and client follow-up to motivate men to stay engaged with PrEP.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies, mostly done in adult women have suggested that delivery in a long-lasting injection would be a good target for drug development [15][16][17][18]. However, given the distinct developmental, physical and social differences between adult women and female adolescents [19], it is essential to explore how the mode of delivery of an HIV prevention option impacts acceptability and use in the adolescent population.…”
mentioning
confidence: 99%